2017
DOI: 10.4103/jos.jos_124_16
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of oral health-related quality of life in orthodontic patients treated with fixed and twin blocks appliances

Abstract: OBJECTIVE:To study the impact of orthodontic treatment on the quality of life in two patient groups, one treated with the twin block appliance and the other with fixed appliances.MATERIALS AND METHODS:Ninety-eight patients, aged between 10 and 16 years, were recruited in the fixed (20 males and 29 females) or functional (29 males and 20 females) treatment groups. The oral health-related quality of life (OHRQoL) was measured before treatment and followed up at the end of the treatment. The instrument used to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…It can be inferred that two of the studies can be rated of low quality. Trials conducted by Alzoubi [ 49 ] and Miamoto [ 50 ] had high selection bias and detection bias. Random sequence generation was unclear in these two studies and the study of Pithon [ 51 ] reflected an acceptable quality (only performance bias was high).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It can be inferred that two of the studies can be rated of low quality. Trials conducted by Alzoubi [ 49 ] and Miamoto [ 50 ] had high selection bias and detection bias. Random sequence generation was unclear in these two studies and the study of Pithon [ 51 ] reflected an acceptable quality (only performance bias was high).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 28 studies included in the study, 26 studies used fixed appliances, whereas two studies used removable devices (1 research: myofunctional and another study: removable appliance with digital springs). The two studies in which were used removable appliances [ 49 , 50 ] were of low quality in quality assessment, whereas in a total of 23 studies analyzed for OHRQoL, fixed appliances showed increase in quality of life in 20 studies [ 21 , 22 , 35 , 36 , 39 , 41 , 42 34 , 51 , 54 58 ] and no improvement of QoL in 3 studies [ 6 , 40 , 53 ]. Three of the studies [ 29 , 59 , 60 ] assessed self-esteem in which only fixed appliances were used; no study was present to analyze the SE with removable appliances.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations